The extent of Implementing Innovation Management in Public Industrial (Journal of Hama University, 2025)
The aim of the research is to determine the extent of innovation management application in public industrial companies in Latakia - namely, the Textile Company, the Public Company for Cotton Yarns in Latakia, and the Coast Thread Company in Jableh. The researcher relied on the SPOLN model developed by Tidd and Bessant (2009), consisting of five dimensions: strategic, operation, organization, learning, and networking. The descriptive approach and analytical method were used as the general research methodology. Data collection involved the researcher using questionnaires and personal interviews as data collection tools. The questionnaires were distributed to all managers responsible for strategy management in the companies under study, with a total of 45 valid questionnaires for analysis. The results indicated that public industrial companies in Latakia do not apply innovation management in its scientific concept.
Keywords: Innovation, Innovation Management, SPONL Model